Potentiation of Ethanol in Spatial Memory Deficits Induced by Some Benzodiazepines - Takiguchi Atsushi; Masuoka Takayoshi; Yamamoto Yasuko; Mikami Azusa; Kamei Chiaki (Elsevier, 2006)
Abstract.: Triazolam caused no significant increase in the total error at 0.05 and 0.1 mg/kg. However, at 0.2 mg/kg, it caused a significant increase in total error. Almost the same findings were observed with brotizolam and rilmazafone. That is, at 0.2 and 0.5 mg/kg of brotizolam, 0.5 and 1.0 mg/kg of rilmazafone caused no significant increase in the total error. However, brotizolam at 1.0 mg/kg and rilmazafone at 2.0 mg/kg caused a significant increase in total error. Triazolam (0.05 mg/kg) and ethanol (1.0 g/kg) showed no significant effect on the numbers of errors when used alone separately, but the simultaneous use of triazolam and ethanol caused a significant increase in total error. Almost the same findings were observed with the coadministration of brotizolam (0.2 mg/kg) or rilmazafone (0.5 mg/kg) with ethanol. These results clearly indicate that all the short-acting benzodiazepines used in the study showed potentiation by ethanol in spatial memory deficits in mice. Keywords:: triazolam, brotizolam, rilmazafone, ethanol, radial maze